Poeta i śmierć - Głombiowska, Zofia (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
The article concerns Klemens Janicki (1516–1543), a Polish poet who wrote in Latin. The author first presents the character and predilections of the poet (iuvenis iocosus), she also stresses – on the basis of Janicki’s own words – the difference of his fortune when compared with the fortune of Ovid (Naso beatus, the exile and the death). Finally, she analyses his vision of God (Pater blandissimus) and heaven, in which he found consolation in a deadly disease.